Fertilizer Response on the Growth and Biomass of a Common Timber Species of Arunachal Pradesh Terminalia myriocarpa (Hollock) Seedlings - Mohan, S. (Indian Forester, 1992)
Inorganic Fertilizer application is known to augment the fertility of soils depleted of nutrients due to various reasons. An experiment to study the response of N, P and K fertilizers on the growth and biomass yield of Terminalia myriocarpa (Hollock) seedlings, which is a common timber species of Arunachal Pradesh was conducted in greanhouse conditions. It is seen that applications of 336 kg/ha of nitrogen, 336 kg/ha of phosphorus and 112 kg/ha of potash increases the growth (height and diameter) and also biomass production (fresh weight and dry weight). This dosage is recommended for application in fields with similar soil conditions as in the experimental soil types.